Comfort evaluation of a subject-specific seating interface formed by vibrating grains. (September 2018) - Liu, Shenghui; Qu, Yunxia; Hou, Shujun; Li, Kai; Li, Xinye; Zhai, Yang; Ji, Yunxiao
Abstract: Sitting is the most common posture for work in offices, and spinal cord injury (SCI) patients who are wheelchair dependent spend 10.6 h per day seated in wheelchairs. Thus, the comfort of subject-specific interfaces is increasingly important for the well-being of patients and office workers. This paper introduces a new method of forming a subject-specific interface, based on vibrating grains. Twenty subjects (10 females and 10 males) participated in the sitting test. Interface comfort was evaluated using the pressure distribution and subjective rating methods. Five seating interface types were compared. The results showed that compared with a flat interface, the interfaces formed by vibrating grains had a significantly reduced peak contact pressure (PeakCP) (by more than 58.03%), and that PeakCP was highly correlated with the comfort rating ( R  = −0.533) and discomfort rating( R  = −0.603). This new method shows promise for guiding the future development of customized seating interfaces. Highlights: A new method of forming a subject-specific interface based on vibrating grains. Interface comfort was evaluated by pressure distribution and subjective rating. Analysis of the correlations between pressure parameters and subjective ratings.